Implementation of Corporate Cash Waqf at PT PLN for Achieving SDGs in Indonesia: A Maqashid Shariah Perspective - Dede Al Mustaqim; Intan Nurul Fadilah (Badan Wakaf Indonesia, 2026)
Corporate-based cash waqf is an innovative form of Islamic philanthropy with significant potential to support sustainable development. The Baitul Maal Foundation of PLN (YBM PLN), established on September 11, 2006, under Director’s Decree No. 132.K/DIR/2006 and No. 133.K/DIR/2006, is one of the pioneers in implementing cash waqf within a corporate environment through fundraising from employees of PT PLN (Persero). This study aims to analyze the implementation of cash waqf managed by YBM PLN in relation to the achievement of the Sustainable Development Goals (SDGs) in Indonesia, viewed from the perspective of Maqashid Sharia. Data show that cash waqf collection reached IDR 87.4 million in 2020, IDR 3,645 million in 2021, IDR 132 million in 2022, and IDR 104.1 million in 2024. The funds are distributed across five main program pillars: humanitarian, health, da’wah, economic empowerment, and education. This research employs a qualitative approach with a case study design on YBM PLN, utilizing document analysis and in-depth interviews with waqf managers. The findings indicate that the implementation of cash waqf at YBM PLN makes a tangible contribution to achieving several SDG targets, particularly poverty alleviation, improving the quality of education, ensuring decent health, and strengthening community economic resilience. Furthermore, the management of cash waqf aligns with the principles of Maqashid Sharia, including the preservation of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-‘aql), lineage (hifz al-nasl), and wealth (hifz al-mal). This study recommends optimizing the corporate cash waqf management model through program diversification, enhanced transparency, and strengthened stakeholder collaboration to generate broader, sustainable, and measurable impacts for society.